Process Of Applying Modified Space Model For Defining Company’s Strategy - Borocki, Jelena (International Journal of Industrial Engineering and Management, 2011)
Today, in innovative economy, in times of blurring boundaries between industries and organizations, companies are facing the new situation: they have to take decisions quickly, despite their importance and despite the incomplete information.Company’s future and its success depends heavily on its strategy which could be defined through different models of strategic planning. Most of the models used for better decision making, better creating strategic plans, give a company a possibility to define a path how to reach its future, determine external and/or internal environment, etc. Modified SPACE model, as a model of strategic planning, is presented in this paper. It is useful in a situation when company want to select key factors for defining its future development and to asses is a proposed change of strategic posture is possible or not. Model is applicable for different type of companies, different size and ownership. Article history: Received (23 February 2011); Revised (05 Jun 2011); Accepted (27 Jun 2011)